Ex-post assessment of merger effects: the case of Pfizer and Pharmacia (2003) - Nina Leheyda; Patrick Beschorner; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The paper studies the effects of the Pfizer and Pharmacia (2003) merger on competition in the Swiss pharmaceutical market and compares the assessment of the Swiss Competition Commission (COMCO) with the post-merger market developments. We find that the merger has had a miniscule impact on the Swiss pharmaceutical market. This has primarily to do with the fact that the product portfolios of both companies have shown no or only slight overlaps. In both cases of potential anticompetitive effects, the companies successfully proposed to divest some of their assets in order to prevent a further strengthening of their dominant position. The remedies included products in the development phase which were not available on the market at the time of the decision. In other markets in which either an overlapping of businesses of both companies existed or in which one of the merging entities held a dominant market position, no significant effects of the merger were noticed. This might have to do with both, existing price regulation in the Swiss drug industry and changes in Pfizer's product portfolio following the merger. Furthermore, with respect to other potentially interesting market characteristics such as investment behaviour, R&D, sales or employment, available data on global company level does not allow an isolation of the possible effects of the merger.
urn:nbn:de:bsz:180-madoc-31866
Keywords: K21; L42; L62; 330; mergers; ex-post evaluation; pharmaceutical markets